2020
DOI: 10.2118/201196-pa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geological Variables in Controlling Oil-Reservoir Performance: An Insight from a Machine-Learning Technique

Abstract: Summary Predicting oilfield performance is extremely challenging because of the large number of variables that can influence and control it. Traditional methods such as decline-curve analysis have been commonly used but have been shown to have significant shortcomings. In recent years, advances in machine learning (ML) have provided a new suite of tools to tackle complex multivariant problems such as understanding oil-reservoir performance and predicating the final recovery factor. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The predictive power of the trained trees can then be evaluated based on the observations that were not used in the training (i.e., out of bag observations). Random forest models are advantageous in that they do not make assumptions about data distribution and the form of the relations between the predictors and response variable and their prediction is mostly insensitive to correlated predictors (e.g., Aliyuda et al., 2020; Konapala & Mishra, 2020; Vaughan et al., 2017). Random forest models are particularly suitable for analysis of complex natural systems that are influenced by multiple factors (e.g., Aliyuda et al., 2020; Cotton et al., 2016; Konapala & Mishra, 2020; Rafat et al., 2021; Vaughan et al., 2017) (a more detailed description of random forest is available in Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…The predictive power of the trained trees can then be evaluated based on the observations that were not used in the training (i.e., out of bag observations). Random forest models are advantageous in that they do not make assumptions about data distribution and the form of the relations between the predictors and response variable and their prediction is mostly insensitive to correlated predictors (e.g., Aliyuda et al., 2020; Konapala & Mishra, 2020; Vaughan et al., 2017). Random forest models are particularly suitable for analysis of complex natural systems that are influenced by multiple factors (e.g., Aliyuda et al., 2020; Cotton et al., 2016; Konapala & Mishra, 2020; Rafat et al., 2021; Vaughan et al., 2017) (a more detailed description of random forest is available in Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have examined the relationship between geological/engineering factors with reservoir performance metrics such as reservoir daily production rate, depletion rate, and recovery factor. The authors in [39] and [40] reported a strong relationship between reservoir performance and reservoir volumes as well as size of the field or reservoir. Similarly, [41] suggested that working gas, base gas, and total gas are the key factors that control the deliverability of underground natural gas storage.…”
Section: The Proposed Sarf Model Development Processmentioning
confidence: 99%